Physical and ultrasonographic diagnosis of intussusception in a crossbred Jersey cow- a case report - M. Venkatesan; P. Tamilmahan; A. Kumaresan; M. Saravanan; Athmakur Venkatesh Rao; N. Premalatha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A six-year-old Crossbred Jersey cow was presented with the complaint of progressive in appetence to complete anorexia, reduction of faeces quantity followed by complete absence of faeces for a period of one week. No improvement was observed to prior medication with parenteral fluids and oral laxatives. The presence of firm mass and malodorous scanty blackish pasty dung, with evincement of pain cranial to the pelvic cavity on right dorsal flank was observed per-rectum. Transabdominal ultrasonography of the firm mass which was positioned per-rectally towards dorsal flank revealed a “bull’s eye appearance”. The intussuscepted intestine measured 4.42 cms in diameter while the inner intussusceptum measured 1.47cm in diameter.. Right flank exploratory laparotomy revealed a jejuno-ileal intussusception and end to end anastomoses was performed following jejuno-ileal resection. The animal had uneventful recovery without any complication and the appetite was restored to normalcy. In conclusion transabdominal ultrasound along with per rectal examination could be a valuable diagnostic tool in cows with intestinal obstruction.